2014
DOI: 10.1155/2014/495219
|View full text |Cite
|
Sign up to set email alerts
|

Providing Care in Emergency Department Hallways: Demands, Dangers, and Deaths

Abstract: Emergency departments (ED) worldwide have experienced dramatic increases in crowding over the past 20 years that now have reached critical levels. One consequence of ED crowding has been the routine use of ED hallways for patient care. This includes ED patients who are awaiting care but are considered unstable to remain in the waiting room, patients who are undergoing active medical and trauma treatment, and patients who have been stabilized but await transfer to an inpatient bed (boarding) or another institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…The genesis of this problem is the closure of most public mental health clinics and residential treatment facilities several years ago from lack of county funding, leaving these patients in a void [47]. Our ED has taken over this role, leading to overcrowding and hallway boarding of ambulatory patients on 72-h psychiatric holds [47][48][49]. Unfortunately, this is not a phenomenon unique to California [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genesis of this problem is the closure of most public mental health clinics and residential treatment facilities several years ago from lack of county funding, leaving these patients in a void [47]. Our ED has taken over this role, leading to overcrowding and hallway boarding of ambulatory patients on 72-h psychiatric holds [47][48][49]. Unfortunately, this is not a phenomenon unique to California [50].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in disposition observed between non-admitted patients may be explained by the unique neuropsychopharmacological properties of cocaine and methamphetamine. Stimulant use disorder in general is associated with a high rate of suicidal ideation and/or attempts, depression, anxiety, and acute psychosis [54][55][56][57][58][59][60][61]. Stimulants are primarily taken for their positive actions, such as enhancement of alertness and emotion [44,62].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the study described hallway nursing as occurring when the inflow of patients exceeded the outflow for an extended period of time. This relationship between crowding and hallway care was also reported by Richards et al (2014), who indicated that caring for patients in these non-clinical settings can result in various negative patient outcomes, such as prolonged hospital stays, absence of consistent monitoring, preventable disability, and dissatisfaction by both patients as well as staff. Participants in this study identified that patients were placed in hallways in order to continue to provide some form of emergency care.…”
Section: Summary Of Findingssupporting
confidence: 55%
“…Licensed ED beds, in theory, provide visual and auditory privacy for HIPAA compliance, either with walls or thick curtains between beds. However, increasing numbers of patients receive ED care in noisy, congested ED hallways, and not licensed beds (37). In the hallway, patients are fully visible to ED staff, patients, and visitors, and may receive compromised care as a complete history and physical examination is usually impossible.…”
Section: Variability Of Ed Facility Feesmentioning
confidence: 99%